Pengaruh Tingkat Literasi Gender Terhadap Konstruksi Gender Di Kabupaten Kediri - Qurrotul'ain, Diah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Gender literacy plays a crucial role in shaping gender justice within society. The level of gender literacy directly influences how gender roles and norms are constructed. Gender literacy is a deeper understanding of gender roles, gender equality, and gender-related issues. A high level of awareness regarding gender equality fosters greater sensitivity toward achieving gender justice. This research adopts a descriptive method, with data collected through a survey using a questionnaire as the primary data collection tool. The findings indicate that the understanding of gender among the community in Kediri Regency is relatively strong. The community has widely embraced gender equality values, which have been disseminated through education and social media. However, patriarchal stereotypes persist, resulting in unequal gender constructions within society. A solid understanding of gender and gender construction can empower the people of Kediri to challenge, explore, and advocate for fairer social changes, ultimately leading to more equitable gender justice. Youth, in particular, can serve as agents of change by advocating for gender equality, educating the public, and actively participating in initiatives that promote gender equality.